2018
DOI: 10.1002/jor.23878
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ADAM10 in satellite cells accelerates muscle regeneration following muscle injury

Abstract: Muscle injury is one of the most common orthopedic and sports disorders. For severe cases, surgical repair may be indicated; however, other than immobilization and the administration of anti-inflammatory drugs there is currently no effective conservative treatment for this condition. Satellite cells (SCs) are muscle-specific stem cells and are indispensable for muscle regeneration after muscle injury. SCs are activated upon muscle injury to proliferate and differentiate into myoblasts, which subsequently fuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…There are few reports on ADAMs in muscle tissue; however, two studies clearly showed that ADAM10 is expressed on muscle cells [ 92 , 93 ]. In order to repair muscle damage caused by excessive exercise or trauma, the proliferation of muscle-specific satellite cells in the muscle fibers and then differentiation are required.…”
Section: Hyper-il-6 and Sgp130 Production During Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…There are few reports on ADAMs in muscle tissue; however, two studies clearly showed that ADAM10 is expressed on muscle cells [ 92 , 93 ]. In order to repair muscle damage caused by excessive exercise or trauma, the proliferation of muscle-specific satellite cells in the muscle fibers and then differentiation are required.…”
Section: Hyper-il-6 and Sgp130 Production During Exercisementioning
confidence: 99%
“…In order to repair muscle damage caused by excessive exercise or trauma, the proliferation of muscle-specific satellite cells in the muscle fibers and then differentiation are required. ADAM10 in muscle satellite cells maintains the satellite cell pool; therefore, the inhibition of ADAM10 activity accelerates satellite cell differentiation [ 93 ]. The expression of ADAM17 in muscle tissue was confirmed and seems to be related to hypoxia [ 94 ].…”
Section: Hyper-il-6 and Sgp130 Production During Exercisementioning
confidence: 99%
“…Therefore, we employed GI254023X, a selective ADAM10 inhibitor that down‐regulates its expression on the surface of the cell membrane 40 . No clinical trials have been conducted to date; however, several animal studies have suggested that GI254023X safely inhibits tumour progression in several malignancies 41–44 . In the present study, GI254023X mimicked the effects of Tspan15 knockdown in HuCCT1 cells with high Tspan15 expression, as GI254023X treatment decreased the expression of surface m‐ADAM10, inhibited Notch1 activation, and suppressed the development of CSC‐like properties and EMT, which inhibited cell invasiveness and chemoresistance against GemCis.…”
Section: Discussionmentioning
confidence: 67%
“…GI254023X has been applied in various animal disease models. Beneficial effects were found in a mouse model of muscle injury and regeneration in which both genetic inhibition of ADAM10 and its pharmacological inhibition by GI254023X accelerated regeneration (Mizuno et al, 2018). In a bacterial sepsis model, GI254023X reduced vascular injury, vascular endothelial (VE) cadherin cleavage and concomitant loss of endothelial barrier function (Powers et al, 2012).…”
Section: Discussionmentioning
confidence: 99%